2016
DOI: 10.1016/j.actatropica.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Aedes ( Stegomyia ) albopictus ’ dynamics influenced by spatiotemporal characteristics in a Brazilian dengue-endemic risk city

Abstract: Brazil reported the majority of the dengue cases in Americas during the last two decades, where the occurrence of human dengue cases is exclusively attributed to the Aedes (Stegomyia) aegypti (Linnaeus). Nowadays, other recognized Dengue virus (DENV) vector in Asian countries, Aedes (Stegomyia) albopictus (Skuse), has been detected in more than half of the 5565 Brazilian municipalities. Therefore, the aim of the present study was to investigate the presence of, and determine the Ae. albopictus’ dynamics influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
0
12
0
2
Order By: Relevance
“…In this country, previous studies identified field-collected immature forms of A. albopictus infected by all DENV serotypes [6,17,19,[45][46][47], and by ZIKV [48]. Despite the variation on the vector competence of A. albopictus according to its geographic origin [49], in other countries this is the only species involved in arboviruses transmission [19,50], including endemic occurrence in rural areas [5], reinforcing the plausibility of a similar event in Brazil.…”
Section: Plos Onementioning
confidence: 62%
See 3 more Smart Citations
“…In this country, previous studies identified field-collected immature forms of A. albopictus infected by all DENV serotypes [6,17,19,[45][46][47], and by ZIKV [48]. Despite the variation on the vector competence of A. albopictus according to its geographic origin [49], in other countries this is the only species involved in arboviruses transmission [19,50], including endemic occurrence in rural areas [5], reinforcing the plausibility of a similar event in Brazil.…”
Section: Plos Onementioning
confidence: 62%
“…In 2019, more than 100 countries were endemic for DENV and 87 had evidence of autochthonous transmission of ZIKV [4]. Brazil is currently the nation with the highest report of DENV [5] and ZIKV infections in the world [4]. There, Aedes aegypti is the only species proven to be involved in the transmission of these viruses [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Do ponto de vista da saúde pública, os mosquitos hematófagos são os principais responsáveis pela transmissão de doenças infecciosas e parasitárias de importância clínica e epidemiológica para o homem, tais como malária, filariose, febre amarela, dengue, Chikungunya e Zika, dentre outras. Esses vetores estão distribuídos em todo território brasileiro e apresentam uma ampla capacidade de adaptação às mudanças climáticas e à invasão do homem ao seu habitat natural (BEZERRA et al, 2016;BOGOCH et al, 2016;CARRINGTON;CAMERON, 2014;GUBLER, 2002). Dentre as espécies de mosquitos de importância médica, Aedes aegypti é a melhor caracterizada até o momento.…”
Section: Atividades Biológicas Dos Componentes Salivares Do Mosquito unclassified